THE ROLE OF THE POLICE IN THE INVESTIGATION OF TRAFFIC ACCIDENT CASES THAT RESULTED IN SERIOUS INJURIES AND DEATHS IN THE MEDAN POLICE TRAFFIC UNIT - Syahri Ramadhan; Isnaini Isnaini; Ridha Haykal Amal (SOSIOEDUKASI, 2026)
Traffic accident cases in Medan City in the last three years show a high number with serious injuries to death. Most of them are caused by driver negligence. This study aims to analyze the legal basis for the settlement of traffic accidents that result in death and the role of investigators of the Medan Police Traffic Unit in the investigation process and legal protection for perpetrators and victims. Using a qualitative descriptive method with a case study approach, the results of the study show that the settlement of these crimes is regulated in various regulations, including the Criminal Procedure Code and Law Number 22 of 2009. Investigators from the Medan Police Traffic Unit play an important role in processing crime scenes and collecting evidence to realize fair and professional law enforcement.